Getting Rid of Interests on Bank Deposits and Loans: A Juristic and Analytical Study - Busari, Saheed Abdullahi (IIUM Press, 2021)
Deposit and loan are important products for Islamic banks because they play important roles in promoting the Islamic economy. Despite the growth of the Islamic economy, especially from the contributions of its financial institution, the interest-based proceeds seem to be a concern to the banking decision-makers because the glorious Islamic. Shariah does not permit dealing with the interest-based balance. Therefore, the study highlights how to get rid of the usury on bank deposits and loans and its shariah rulings. The study employed the inductive approach in gathering and arranging information. It also uses the descriptive method in explaining the basic terms in the research. This research aims to shed light on the reality of the usury balance in the bank deposits and loans, with a special focus on how to dispose of the usurious interest in banking. The necessity of the modern financial activities shows no one can dispense with the banking financial transaction. Moreover, the main significance of disposing the prohibited interest-based balance is blocking the potential means towards consumption of usury or dealing with interest.